"They Can't See Me Smile": Communication and Relationship Challenges of Providing Home Care During a Pandemic. Issue 1 (2nd January 2023) - Scott, Muriel; Kendall, Peggy
ABSTRACT: Providing home care to individuals with intellectual and developmental disabilities can be challenging in the best of times. Communication and relationships, which are both critical to the care provided by Direct Support Professionals (DSPs), were impacted significantly during the COVID-19 pandemic. Using interpretive research methods with DSPs at a Midwestern agency, this study identifies communication and relationship challenges brought on by the COVID-19 pandemic and strategies used to manage those challenges. COVID-19 protocols like masking, cleaning procedures, and cared-for individuals' home confinement created significant relational challenges including misunderstandings, changing routines, and fluctuating roles. DSPs also discussed how those challenges were overcome, including communication adaptation, creativity, and empathy. By examining the strategies DSPs used to negotiate the challenges and their changing roles, insight can be gained into how organizations might best support direct care workers in times of significant stress and uncertainty. This study builds on the growing scholarship exploring the impact of COVID-19 on health care communication.